Discrimination Against Belief Towani Tolotang Society in the Implementation of Constitutional Law on Human Rights - Sari, Intan Puspita (The Indonesian Journal of International Clinical Legal Education, 2021)
Freedom of religion has taken place in the constitution of the state of Indonesia namely the 1945 Constitution Article 28E paragraph (2). In fact, the implementation of the law on the exercise of freedom in embracing Caste is still often treated differently. You should be commonplace because of the many factors that affect the various tribes, cultures and beliefs in Indonesia. Since this already exists, the Towani Tolotang people who are believers demand rights to the local people not to discriminate against them. This study is expected to contribute to the improvement and affirmation of the constitutional law on Human Rights.